Comparative Analysis of Anticancer and Antibacterial Activities among Seven Trametes Species - Nguyen, Ha Thi Kim; Lee, Jiwon; Park, Yejin; Park, Hyon Jin; Ahn, Soon Kil; Kim, Jae Kwang; Kang, Dong-Ku; Kim, Minkyeong; Ahn, Chorong; Kim, Changmu; Choi, Jaehyuk (Mycobiology, 2023)
Species in the genus Trametes (Basidiomycota, Polyporales) have been used in natural medicine for a long time. Many studies reported that mycelia or fruiting bodies of Trametes spp. exhibited effects of antioxidant, anti-inflammatory, anticancer, and antimicrobial activities. However, comparative analysis in this genus is scarce due to limitation of morphological identification and the sample number. In this study, the 19 strains of seven Trametes species were chosen to generate a five-gene-based phylogeny with the 31 global references. In addition, 39 culture extracts were prepared for 13 strains to test for anticancer and antibacterial activities. Strong anticancer activities were found in several extracts from T. hirsuta and T. suaveolens. Anticancer activities of T. suaveolens, T. cf. junipericola and T. trogii were first described here. The antibacterial ability of T. versicolor and T. hirsuta extracts has been confirmed. The antibacterial activities of T. suaveolens have been reported at the first time in this study. These results suggest an efficient application of the genus Trametes as the drug resources especially for anticancer agents.Species in the genus Trametes (Basidiomycota, Polyporales) have been used in natural medicine for a long time. Many studies reported that mycelia or fruiting bodies of Trametes spp. exhibited effects of antioxidant, anti-inflammatory, anticancer, and antimicrobial activities. However, comparative analysis in this genus is scarce due to limitation of morphological identification and the sample number. In this study, the 19 strains of seven Trametes species were chosen to generate a five-gene-based phylogeny with the 31 global references. In addition, 39 culture extracts were prepared for 13 strains to test for anticancer and antibacterial activities. Strong anticancer activities were found in several extracts from T. hirsuta and T. suaveolens. Anticancer activities of T. suaveolens, T. cf. junipericola and T. trogii were first described here. The antibacterial ability of T. versicolor and T. hirsuta extracts has been confirmed. The antibacterial activities of T. suaveolens have been reported at the first time in this study. These results suggest an efficient application of the genus Trametes as the drug resources especially for anticancer agents.